The Effect of Effective Factors on Consumer Behavior in Iran\'s Best Shopping Centers Based on the Principles of Urban Management - mahmood samadi; mahmoud nooraei; Mohammad mehdi Mozaffari; babak haji karimi (تحقیقات کاربردی علوم جغرافیایی)
The importance of retail in the marketing process has become weaker with the development of shopping centers today, The growth of shopping malls in the metropolitan areas of Iran has been increasing over the past few years and there is no longer competition for retailers. Therefore, surveying the behavior of consumers in their shopping centers is a competitive strategy for the owners of these industries in order to compete with retailers and other shopping centers. The statistical population in this research is Shopping centers of Tehran, Isfahan, Alborz and Mazandaran. The method of selecting shopping centers based on artificial intelligence studies has been done through genetic algorithm. The criteria for choosing the centers are optimal according to the principles of urban management. Using a conceptual model through structural equations of partial least squares, using the Smart PLS software, the statistical population of the study was 384 people. The results showed that the variables of beauty, escape, role play, comfort, brand identity, social responsibility, and impunity affect consumers' behavior in shopping centers, The results of this study have been able to provide a native model with respect to the structures of shopping centers in Iran.